Modeling of electromagnetic wave penetration in a human head due to emissions from cellular phone - Ismail, Nurulhuda (2007)
Nowadays, cellular phone becomes a necessity for human being due to its mobility, small size and useful applications provided in the chip. In a long term use, the user will be exposed to the high frequency EM radiation that possibly causes serious illnesses such as alzheimer and brain cancer. Increasing exposure from this radiation is a growing concern for the community to investigate the effects of the emissions to human health. While cellular phone is in used, the energy is transferred from the applied electric field to the human head in the form of kinetic energy of charged particles. The rate of change of the energy transferred is called the absorbed power or Specific Absorption Rate (SAR). SAR values are of key importance when validating possible health hazard and these values are compared with a safety limit set by International Commission on Non-Ionizing Radiation Protection, ICNIRP to ensure that the phone is safe to use. In this study, Finite Difference Frequency Domain (FDFD) technique was used to evaluate the electric field and SAR distribution in a human head due to the emissions from cellular phone that operates at 900 MHz. The numerical results were compared with the CST Microwave Studio software which is based on FDTD method. The results demonstrated that FDFD is not an efficient method to evaluate E field and SAR due to its limitation and imperfect boundary condition. On the other hand, the CST Microwave Studio results show that magnitude of EM field decreases exponentially with the penetration distance at a rate specified by the attenuation constant, a. Besides, the SAR is affected by operational frequency of the phone and the electrical properties of human head. Since FDFD technique can work only for 2D models, it is recommended that a fast and efficient numerical technique need to be studied for 3D human head model and an experimental technique on SAR distribution needs to be done to validate the results from simulation technique.